The frog prince - Grimm, Brothers (England Usborne publications, 2005)
Princess Poppy really doesn't want to marry Prince Humperdink. She is hoping a handsome prince will come and rescue her. Instead, she ends up with a slimy frog--but might there be more to this frog than meets the eye?
The Frog Prince" tells the classic fairy tale of a spoiled princess who reluctantly befriends a frog, who is actually a prince under a spell. Through her eventual kindness, the spell is broken, and they live happily ever after. Location: 3A
Keywords: Frog prince